2015
DOI: 10.1007/s10995-015-1888-6
|View full text |Cite
|
Sign up to set email alerts
|

Sleep-Related Infant Deaths in Victoria: A Retrospective Case Series Study

Abstract: Given the case series nature of the study design, a causal relationship between bed-sharing and infant death could not be inferred. However the fact that nearly half of all sleep-related deaths occurred in the context of bed-sharing, provides strong support for the need to undertake definitive analytic studies in Australia so that evidence-based advice can be provided to families regarding the safety of bed-sharing practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…For example, a study in the US showed that the unintentional suffocation deaths of infants aged 0–3 months accounted for nearly 60% of the cases [ 21 ]. In Australia, infants under 4 months were involved in more than 90% of unintentional suffocation deaths [ 22 ]. Regarding the high incidence of unintentional suffocation in infants, the most likely explanation is the imperfect physiological functions of newborns and infants and poor care by parents, which leads to asphyxia in bedding or improper feeding and asphyxia caused by foreign bodies in the respiratory tract [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, a study in the US showed that the unintentional suffocation deaths of infants aged 0–3 months accounted for nearly 60% of the cases [ 21 ]. In Australia, infants under 4 months were involved in more than 90% of unintentional suffocation deaths [ 22 ]. Regarding the high incidence of unintentional suffocation in infants, the most likely explanation is the imperfect physiological functions of newborns and infants and poor care by parents, which leads to asphyxia in bedding or improper feeding and asphyxia caused by foreign bodies in the respiratory tract [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The current public health Safe Sleeping program contains six key messages: 1) Sleep baby on back; 2) Keep head and face uncovered; 3) Keep baby smoke free before and after birth; 4) Safe sleeping environment night and day; 5) Sleep baby in safe cot in parents' room; 6) Breastfeed baby [19,20]. Despite Australia's national evidence-based health promotion program, inconsistencies exist amid the many forms of advice families receive, with each state and territory's Health Department developing their own slightly modified policies and guidelines [17,[21][22][23]. This is especially so for those messages which have an emerging or developing evidence-base, such as shared sleeping, infant wrapping, and dummy use.…”
Section: Introductionmentioning
confidence: 99%
“…Of the sudden unexpected infant deaths and accidental suffocation and strangulation in bed (ASSB, ICD-10-W75) incidents, 20%-80% occurred during co-sleeping. The mean age at the time of occurrence was 3.8 months in the United States (Gaw et al 2017), while infants under 6 months were involved in more than 90% of deaths/accidents in Australia (Bugeja et al 2016) consistent with more frequent occurrence at a lower age. On the basis of these reports and the results of the present study, co-sleeping was shown to increase the risk for infant suffocation incidents during early infancy, with some incidents potentially leading to deaths/accidents.…”
Section: Frequency Of Incidents and Factors Related To Infant Suffocamentioning
confidence: 75%
“…There were 21 reports of infant suffocation associated deaths/accidents with co-sleeping in Japan and other countries (Table 5: Nixon et al 1995;Drago and Dannenberg 1999;Nakamura et al 1999;Kemp et al 2000;Thogmartin et al 2001;Aoki et al 2006;Takatsu et al 2007;Kikuchi et al 2008;Blabey and Gessner 2009;Senter et al 2010;Weber et al 2012;Brixey et al 2011;Schnitzer et al 2012;Suzuki et al 2014;Colvin et al 2014;Sauber-Schatz et al 2015;Bugeja et al 2016;Thompson and Moon 2016;Chu et al 2016;Kassa et al 2016;Gaw et al 2017). Of the sudden unexpected infant deaths and accidental suffocation and strangulation in bed (ASSB, ICD-10-W75) incidents, 20%-80% occurred during co-sleeping.…”
Section: Frequency Of Incidents and Factors Related To Infant Suffocamentioning
confidence: 99%